2018
DOI: 10.1055/s-0038-1675833
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Early Antibiotic Exposure and Short-Term Growth Velocity in Premature Neonates

Abstract: Objective To characterize the relationship between the duration of antibiotic administration during the first week of life and subsequent growth velocity during hospitalization. Study Design This was a retrospective study comparing the inhospital growth of infants born between 30 and 326/7 weeks' gestational age (GA) admitted to the Montefiore Weiler and Wakefield neonatal intensive care units between January 2009 and December 2015. Antibiotic duration during the first week of life was classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…On the other hand, in a retrospective study conducted by Reid et al to investigate the correlation between early exposure to antibiotics and the growth rate of preterm neonates, no significant correlation was found between neonate weight and duration of antibiotic therapy (9). In the present study, 438 neonates who were eligible for the study were divided into three groups: the first group consisted of 58 neonates who did not receive any antibiotics, the second group entailed 304 neonates receiving antibiotic therapy for less than five days, and the third group contained 69 neonates receiving more than five days of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, in a retrospective study conducted by Reid et al to investigate the correlation between early exposure to antibiotics and the growth rate of preterm neonates, no significant correlation was found between neonate weight and duration of antibiotic therapy (9). In the present study, 438 neonates who were eligible for the study were divided into three groups: the first group consisted of 58 neonates who did not receive any antibiotics, the second group entailed 304 neonates receiving antibiotic therapy for less than five days, and the third group contained 69 neonates receiving more than five days of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, almost every very preterm-birth neonate is exposed to a variable duration of antibiotics in the NICU [8,18]. While most studies investigate the effects of early-life antibiotic exposure on growth outcomes in term-birth infants [3,5,19], few have examined these effects in preterm-birth children [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In infants born at 30-32 weeks of gestation, Reid et al [22] characterized the relationship between the duration of antibiotic exposure in the first week of life and subsequent growth velocity during hospitalization. They found no distinction in the zBW among the groups with no antibiotics, <5 days of antibiotics, or ≥5 days of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic exposure during pregnancy has been related to long-term changes in the gut microbiota, which may result in reduced growth in males during the first six years of life, according to this research ( 54 ). Another study revealed that early antibiotic exposure was not connected with enhanced growth velocity between delivery and discharge in neonates and infants in intensive care units inpatient antibiotics ( 55 ).…”
Section: Gut Microbiota and Linear Growthmentioning
confidence: 99%
“…They have complicated interactions with each other. This review mostly includes cohort studies ( 26 , 28 , 30 , 39 , 41 , 44 , 45 , 48 , 53 , 54 , 56 , 59 ), cross-sectional studies ( 31 , 37 , 46 , 51 , 71 , 76 , 78 ), case-control studies ( 29 , 47 , 55 , 57 , 62 ), and some animal studies focusing on particular mechanisms ( 48 , 87 , 88 ). Although the data supports a link between intestinal flora and linear development in children, our review has limitations that prohibit us from fully verifying the causal relationship between gut flora and linear development in children.…”
Section: Limitationsmentioning
confidence: 99%